Angiopoietin-2 expression in patients with an acute exacerbation of idiopathic interstitial pneumonias. (August 2016) - Ando, Masaru; Miyazaki, Eishi; Abe, Tetsutaro; Ehara, Chihiro; Goto, Akihiro; Masuda, Taiki; Nishio, Suehiro; Fujisaki, Hideaki; Yamasue, Mari; Ishii, Toshihiro; Mukai, Yutaka; Ito, Takeo; et al.
Abstract: Background and objective: We hypothesized that increased pulmonary vascular permeability may play a role in the pathogenesis of an acute exacerbation of the idiopathic interstitial pneumonias (AE-IIPs). Angiopoietin-2 (Ang-2) promotes endothelial activation, destabilization, and inflammation. The purpose of this study was to examine whether Ang-2 expression was associated with the pathogenesis of AE-IIPs. Methods: Twenty-three patients with AE-IIP patients, 18 acute lung injury/acute respiratory distress syndrome (ALI/ARDS) patients, 37 idiopathic pulmonary fibrosis (IPF) patients, and 33 healthy volunteers (HVs) were enrolled. The serum level of Ang-2 was measured by an enzyme-linked immunosorbent assay. Results: The serum levels of Ang-2 were higher in AE-IIPs and ALI/ARDS patients than in IPF patients and HVs; the BALF levels of Ang-2 were also higher than in IPF patients. There was a positive correlation between the serum level of Ang-2 and the CRP in patients with AE-IIP patients, whereas a significant positive correlation was found between the serum Ang-2 level and the CRP or SOFA scores of the ALI/ARDS patients. Although the baseline Ang-2 level was not related to survival, the Ang-2 levels significantly declined in survivors during treatment, while they did not change in non-survivors. Conclusions: Increased pulmonary vascular permeability and inflammation due to Ang-2 may play a role in the pathogenesis of AE-IIPs. Highlights: The serum levels of Ang-2 were higher in AE-IIPs than in IPF patients and HVs; the BALF levels of Ang-2 were also higher than in IPF patients. There was a positive correlation between the serum level of Ang-2 and the CRP in patients with AE-IIP patients. The Ang-2 levels significantly declined in survivors during treatment, while they did not change in non-survivors. Increased pulmonary vascular permeability and inflammation due to Ang-2 may play a role in the pathogenesis of AE-IIPs.